Trimebutine Promotes Glioma Cell Apoptosis as a Potential Anti-tumor Agent - Fan, Yi-pu; Liu, Pei; Xue, Wei-kang; Zhao, Wei-jiang; Pan, Hong-chao (Frontiers in Pharmacology, 2018)
Gliomas are the most common primary brain tumors with a usually fetal malignancy. They are associated with a poor prognosis although multiple therapeutic options have been available. Trimebutine is one of the prokinetic agents and it has been mainly used for treatment of disorders of the gastrointestinal (GI) tract such as irritable bowel syndrome. However, its effects on glioma cells remain unknown. Here, we used various concentrations of trimebutine to treat SHG44, U251, and U-87 MG human glioma/glioblastoma cells. And combined experiments of MTT, colony formation assay, and wound healing assay, as well as western blot and immunofluorescence staining were used to evaluate the effects of trimebutine on glioma cells. The results demonstrated that trimebutine significantly inhibited cell viability and colony formation. A significant inhibition of glioma cell migration was also indicated by wound healing assay. In addition, trimebutine promoted cell apoptosis and induced Bcl-2 downregulation, accompanied with Bax upregulation. Both immunofluorescence staining and western blot results showed that Trimebutine increased the level of active Caspase-3. Moreover, trimebutine reduced the activation of both AKT and ERK signaling pathways. In subcutaneous U-87 MG cell xenograft tumors in nude mice, trimebutine significantly inhibited tumor growth. More TUNEL-positive apoptotic cells in tumor sections were observed in trimebutine-treated mice when compared to the vehicle control. Reduced Bcl-2 and upregulated Bax, as well as perturbed p-AKT and p-ERK signaling pathways were also observed in trimebutine-treated xenograft tissues. Our combined data indicated that trimebutine may be potentially applied for the clinical management of glioma/glioblastoma.